2015
DOI: 10.1021/acscatal.5b02205
|View full text |Cite
|
Sign up to set email alerts
|

Role of ZrO2 in Promoting the Activity and Selectivity of Co-Based Fischer–Tropsch Synthesis Catalysts

Abstract: The effects of Zr promotion on the structure and performance of Co-based Fischer-Tropsch synthesis (FTS) catalysts were investigated. Inclusion of Zr in the catalysts was found to increase the FTS turnover frequency and the selectivity to C5+ hydrocarbons and to decrease the selectivity to methane under most operating conditions. These improvements to the catalytic performance are a function of Zr loading up to an atomic ratio of Zr/Co = 1.0, above which the product selectivity is insensitive to higher concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 56 publications
7
42
0
Order By: Relevance
“…[18] The higher activity of hcp Co nanoparticles is identified from various favorable active sites on exposed facets that not available for fcc Co nanoparticles. In addition, Ge et al have proposed that the corrugated Co (10)(11)(12) and Co (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) surfaces can significantly enhance the reactivity toward CO dissociation by reducing the activation barrier compared to the flat Co(0001) and corrugated Co (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) surfaces. [19] The identification of the first CÀ C bond formation in chain growth by Su et al revealed that the preferential carbide mechanism on Co(10-11) is more selective to chain growth rather than methanation, while the preferential CO insertion mechanism on Co(0001) is opposite.…”
Section: Introductionmentioning
confidence: 99%
“…[18] The higher activity of hcp Co nanoparticles is identified from various favorable active sites on exposed facets that not available for fcc Co nanoparticles. In addition, Ge et al have proposed that the corrugated Co (10)(11)(12) and Co (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) surfaces can significantly enhance the reactivity toward CO dissociation by reducing the activation barrier compared to the flat Co(0001) and corrugated Co (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) surfaces. [19] The identification of the first CÀ C bond formation in chain growth by Su et al revealed that the preferential carbide mechanism on Co(10-11) is more selective to chain growth rather than methanation, while the preferential CO insertion mechanism on Co(0001) is opposite.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Rohr et al [15] found that the effect of Zr on the catalyst activity at high pressure FTS conditions was not as significant as its effect at low pressure conditions. Johnson and Bell [33] also observed that the promoting effect of Zr on Co/SiO 2 was already very small at syngas pressures of 10 bar and a temperature of 210 °C. This decreasing promoting effect of Zr with increasing pressure, together with a faster deactivation, may explain the low performance of the CoZrAl ME catalyst.…”
Section: Activity and Stability Of The Catalystsmentioning
confidence: 92%
“…Unfortunately, these results cannot be explained by differences in support acidity, factor that is believed to play a crucial role in the FTS activity [46,47]. According to Johnson and Bell [33], promotion with Zr originates from sites with enhanced activity at the Co-ZrO 2 interface. The results are therefore surprising since a larger contact between ZrO 2 and cobalt and thus, a higher activity, was expected for the CoZrAl ME catalyst.…”
Section: Activity and Stability Of The Catalystsmentioning
confidence: 98%
See 1 more Smart Citation
“…Model catalysts based on Rh exhibit a unique selectivity to oxygenates due to moderate ability for CO dissociation [6,8,[10][11][12][13]. Here, a variety of transition metals were identified as efficient dopants, e.g., Mn, Fe, Co, Mo, or Zr [8,[14][15][16].…”
Section: −1mentioning
confidence: 99%